SPREADING ANALYSIS OF PHENOL, OIL AND GREASE OFPRODUCED WATER FROM OIL AND GAS FIELD AND THEIR IMPACTS TO OFFSHORE ENVIRONMENT - Ramos M, Yovita; Muntalif, Barti Setiani; Muin, Muslim (ITB Journal Publisher, LPPM ITB, 2009)
Abstract: Sea is one of natural resources, which has potential to provide human needs. However, due to resident growth and there are many industries have activities, the sea is started to be polluted and negative impact to people and environment is arisen. One of industry, which has potential to pollute Indonesian sea, is oil and gas production in Natuna Sea. Produced water, which is produced by oil and gas production process in PT. Star Energy, may contain few contaminant constituents including phenol, oil and grease. Distribution of phenol and oil and grease is done using MuQual3D software, which includes hydrodynamic model and qualitative water model. Simulation of phenol distribution and oil and grease from produced water is done for a year for each discharge location within two layers of sea water layer which are mean sea water layer and sea bottom layer. Phenol concentration spreading at the depths of 7 m and 75 m such as 0.012 - 0.14 µg/L, where as oil and grease concentration such as range between 0.15-1.7 µg/L. These spreading simulations show that produced water discharge have complied the sea water quality standard for aquatic biota. From laboratory results of aquatic biota for phytoplankton and zooplankton, are indicated that there is occurrence of ecological pressure within the aquatic area, but still in moderate and stable condition, which means that it could be changed according to the surrounding environment. Where as, from Chanos chanos toxicological model simulation about 9.53-10.12% of study area has impacted. For balancing the ecosystem of Natuna sea, produced water discharge management and other research for aquatic biota in study area are needed.Key words: Produced Water, Phenol, Oil and Grease, Impacts, MuQual3D, Natuna Sea Abstrak: Laut merupakan salah satu sumber daya alam yang berpotensi untuk memenuhi kebutuhan manusia. Namun seiring dengan pertumbuhan penduduk dan banyaknya industri yang beroperasi, laut mulai tercemar sehingga timbul dampak negatif terhadap manusia dan lingkungan. Salah satu industri yang berpotensi dalam mencemari laut Indonesia,khususnya Laut Natuna adalah industri minyak dan gas bumi. Air terproduksi yang dihasilkan oleh proses produksi minyak dan gas di PT. Star Energy, mengandung beberapa senyawa kontaminan termasuk fenol dan oil and grease. Penyebaran fenol dan oil and grease dilakukan menggunakan software MuQual3D yang mencakup model hidrodinamika dan model kualitas air. Simulasi penyebaran fenol, oil and grease dari air terproduksi dilakukan selama 1 (tahun) untuk masing-masing lokasi pembuangan dalam 2 (lapisan air laut) yaitu lapisan permukaan dan lapisan dasar laut. Penyebaran konsentrasi fenol pada kedalaman 7 m dan 75 m berkisar antara 0.012 - 0.14 µg/L sedangkan konsentrasi oil and grease berkisar antara 0.15-1.7 µg/L. Hasil simulasi penyebaran tersebut menunjukkan air terproduksi yang dibuang masih berada di dalam baku mutu. Dari hasil pengukuran plankton, baik fitoplankton maupun zooplankton diperoleh bahwa terdapat tekanan ekologis terhadap struktur komunitas laut, namun masih dalam kondisi yang moderat atau stabil, artinya dapat berubah sesuai dengan keadaan lingkungan sekitarnya. Sedangkan dari hasil simulasi model toksikologi Chanos-Chanos didapat sekitar 9.53% sampai dengan 10.12% wilayah yang terkena dampak pembuangan air terproduksi. Untuk menjaga kestabilan ekosistem Laut Natuna diperlukan pengelolaan pembuangan air terproduksi dan penelitian lebih lanjut untuk biota laut di wilayah studi.